Curcumin-loaded Polyethyleneimine and chitosan polymer-based Mucoadhesive liquid crystalline systems as a potential platform in the treatment of cervical Cancer - Victorelli, Francesca Damiani [UNESP]; Fioramonti Calixto, Giovana Maria [UNESP]; Santos, Karen Cristina dos [UNESP]; Buzza, Hilde Harb; Chorilli, Marlus [UNESP] (Elsevier B.V., 2021)
Cervical cancer is the fourth most common cancer in women. Conventional treatments involve surgery, radiotherapy and radiochemotherapy, which affect negatively the life quality. Bioactive molecules, such as curcumin (CUR), are potential alternatives for cervical cancer treatment. However, CUR has limited solubility in water, thus it is interesting to develop drug delivery systems to improve its clinical use. Here, we propose a liquid crystalline system (LCS) as a medium for the formulation and vaginal administration of CUR. To the best of our knowledge, this is the first study that showed the effect of vaginal mucus on the behavior of the liquid crystalline system as well as the antiangiogenic effect of curcumin incorporated in this system in the CAM model. We formulated LCS based on oleic acid, ethoxylated and propoxylated cetyl alcohol and aqueous phase containing water (FW) or dispersion of chitosan associated with polyethyleneimine (FPC). The characterization methodology revealed that LCS presented a lamellar mesophase, which remained stable in the presence of CUR and artificial vaginal mucus. Rheological, texture, and mucoadhesive tests showed that FPC demonstrated properties desirable for vaginal formulations. In vitro release and ex vivo permeation and retention validated the controlled-release properties of the system. LCS released approximately twice as much CUR as the control in 12 h, while ex-vivo porcine vaginal mucosa retained about 2.3% of CUR from LCS.These formulations revealed biocompatibility for L929 cells and toxicity for Hela cells. The vascular changes in response to this potential treatment were evaluated using the chick embryo chorioallantoic membrane (CAM) as a model. The caliber and the number of vessels reduced after the application of CUR-loaded formulations, encouraging the application of the mucoadhesive LCS developed for cervical cancer treatment. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Pharmaceutical nanotechnology; Liquid crystalline systems; Mucoadhesion; Curcumin; Vaginal administration; Cervical cancer